2021
DOI: 10.3389/fphar.2021.719802
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Improvement in 2-Year Survival Rate of Patients with Stage II-III Non-Small Cell Lung Cancer Treated with Different Durations of Chinese Patent Medicine: A Retrospective Cohort Study

Abstract: Background: Chinese patent medicine is widely used among patients with malignant tumors, and current studies have shown that long-term treatment with Chinese patent medicine is related to improved outcomes of patients. Huisheng Oral Liquid is a kind of Chinese patent medicine with the effects of curing dispersion-thirst and dissipating blood stasis. However, little is known about how it affects the survival rate of patients. Thus, patients with stage II-III NSCLC (non-small-cell lung cancer) were chosen to par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…The median survival time of patients who received HSOS intervention more than 3 months was longer than that of patients who received HSOS less than 3 months. Patients with elevated preoperative FIB level (more than 4 g/L) and those did not undergo surgery had a higher probability of cancer death, which was consistent with our previous study [ 30 , 31 ]. Our previous study revealed that more than 3 months treatment of CPM/HSOS could improve 2-year survival rate of patients with stage II–III NSCLC, and preoperative FIB level more than 4 g/L was a risk factor for the prognosis [ 30 ].…”
Section: Discussionsupporting
confidence: 91%
“…The median survival time of patients who received HSOS intervention more than 3 months was longer than that of patients who received HSOS less than 3 months. Patients with elevated preoperative FIB level (more than 4 g/L) and those did not undergo surgery had a higher probability of cancer death, which was consistent with our previous study [ 30 , 31 ]. Our previous study revealed that more than 3 months treatment of CPM/HSOS could improve 2-year survival rate of patients with stage II–III NSCLC, and preoperative FIB level more than 4 g/L was a risk factor for the prognosis [ 30 ].…”
Section: Discussionsupporting
confidence: 91%
“…For other samples between consecutive qc a and qc b , the correction factors F(i, sample) were obtained by linear interpolation between F(i, qc a ) and F(i, qc b ). (v) Features of each sample were divided into four parts 1 to 4 according to the magnitudes of peak areas: <10 4 , 10 4 − 10 5 , 10 5 −10 6 , and >10 6 . Peak areas in each part were normalized to the 10,000/sample for total useful signals.…”
Section: Data Analysis Methodsmentioning
confidence: 99%
“…Lung cancer is the leading cause of cancer death and the second most commonly diagnosed cancer worldwide with an estimated 2.2 million new cases and 1.8 million deaths in 2020. , The major histological type of lung cancer is non-small cell lung cancer (NSCLC), which accounts for about 85% . Main subtypes of NSCLC include adenocarcinoma (AC), squamous cell carcinoma (SCC), and large cell carcinoma of the lungs, accounting for about 50, 35, and 15% in NSCLC patients, respectively. , The 5-year survival rate of NSCLC is merely 15% . Early detection of lung cancer can improve the 5-year survival rate to 55%, but this is difficult due to the hidden symptoms in its early stages, , and 70% of NSCLC patients were diagnosed at advanced stages …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lymphocytes play an important role in the immune response of the body, while tumor proliferation is often accompanied by a decrease in lymphocytes, and a further increase in the likelihood of a poor prognosis as well (Kara et al, 2017). Fib prediction plays an important role in the prognosis of other malignant tumors (Mi et al, 2017; Sharma et al, 2021; Wang, Jia, et al, 2021; Wang, Wang, et al, 2021; Xu et al, 2021). In this study, the ROC curve was based on the preoperative Fib of patients with oral cancer in southwest China.…”
Section: Discussionmentioning
confidence: 99%